STAT3 Suppresses Cardiomyocytes Apoptosis in CVB3-Induced Myocarditis Via Survivin - Wang, Qiaoyu; Zhu, Qiongjun; Ye, Qiaofang; Wang, Jiajun; Dong, Qianqian; Chen, Youran; Wang, Minna; Fu, Yu; Wu, Rongzhou; Wu, Tingting (Frontiers in Pharmacology, 2021)
Background: Viral myocarditis (VMC) is a common inflammatory cardiovascular disease with unclear mechanisms, which mainly affects children and adolescents. Apoptosis is the key to CVB3-induced myocarditis, and blocking this process may be beneficial to the therapy of VMC. Hence, this study aimed to explore the protective function of STAT3 on cardiomyocyte apoptosis of VMC and its underlying mechanisms. Methods and Results: In this research, we confirmed that STAT3 was significantly activated in both animal and cell models of VMC. To further clarify what role did STAT3 play in VMC, AG490, an inhibitor of STAT3, was used to suppress p-STAT3. Our results demonstrated that decreased expression of p-STAT3 caused by AG490 significantly aggravated severity of VMC with elevated myocardial inflammation, deteriorative ventricular systolic function and increased mortality. It suggested that STAT3 plays a protective role in VMC. To further identify the anti-apoptosis impact that activated STAT3 made, we constructed lentivirus to regulate the expression of STAT3 in NMCs. We found that up-regulated activated STAT3 attenuated cardiomyocyte apoptosis, but down-regulated one aggravated that, which verified activated STAT3 played an anti-apoptosis role in VMC. Following that, we explored what elements are involved in the anti-apoptotic mechanism of activated STAT3 by using survivin inhibitor YM155. The result showed the anti-apoptotic effect of activated STAT3 does not work in the case of survivin inhibition. Conclusions: Our findings demonstrated STAT3 by targeting survivin alleviated cardiomyocyte apoptosis in CVB3-induced myocarditis.